2012
DOI: 10.1002/pi.4263
|View full text |Cite
|
Sign up to set email alerts
|

A facile route to develop electrical conductivity with minimum possible multi‐wall carbon nanotube (MWCNT) loading in poly(methyl methacrylate)/MWCNT nanocomposites

Abstract: Today, we stand at the threshold of exploring carbon nanotube (CNT) based conducting polymer nanocomposites as a new paradigm for the next generation multifunctional materials. However, irrespective of the reported methods of composite preparation, the use of CNTs in most polymer matrices to date has been limited by challenges in processing and insufficient dispersability of CNTs without chemical functionalization. Thus, development of an industrially feasible process for preparation of polymer/CNT conducting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 44 publications
0
24
0
Order By: Relevance
“…Immense research interest has been focused on polymer/carbon nanotube (CNT) nanocomposites in the last few decades because of their dramatically improvement in properties relative to neat polymer and to yield multifunctional materials . The high aspect ratio of CNTs allows property enhancement at lower concentrations as compared with conventional filler particles such as carbon black or nanoclays.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Immense research interest has been focused on polymer/carbon nanotube (CNT) nanocomposites in the last few decades because of their dramatically improvement in properties relative to neat polymer and to yield multifunctional materials . The high aspect ratio of CNTs allows property enhancement at lower concentrations as compared with conventional filler particles such as carbon black or nanoclays.…”
Section: Introductionmentioning
confidence: 99%
“…Various thermoplastics, such as poly(methyl methacrylate) (PMMA), polycarbonate (PC), etc. have been used to prepare polymer/CNT nanocomposites with improved electrical properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the lower frequency region, dielectric loss was increased with increase in CNT loading, while a marginal effect was found at higher frequency. It has already been reported that, with increase in conducting filler loading, dielectric loss increases at lower frequency .…”
Section: Resultsmentioning
confidence: 87%
“…Thus, a very high conductivity in the polymer/CNT nanocomposites can be achieved at very low loadings of CNTs. The efficient dispersion of CNT into the polymer matrix is very difficult to achieve due to the high van der Waals forces between the individual CNT [13]. The small size and large surface area of the CNT lead to such high van der…”
Section: Introductionmentioning
confidence: 99%